Are we safer from terrorist attacks since 9/11? - Lopes, J. (EuroDefence Portugal, 2023)
In 2023, twenty-two years after “the most lethal act of non-state terrorism act”, are we safer from terrorist attacks? There are multiple ways to address this vast question: this text briefly debates some hypothesis, taking into account the phenomenon of transnational terrorism, while looking at the European Union context. As argued elsewhere, here we define terrorism as violence perpetrated by non-state actors against a state, in order to achieve political aims. We begin with a brief analysis of the evolution of the terrorist threat.